2018
DOI: 10.3325/cmj.2018.59.224
|View full text |Cite
|
Sign up to set email alerts
|

Preponderance of microbial isolates among heart transplantation recipients requiring renal replacement therapy: a propensity score-adjusted analysis

Abstract: AimTo assess the association between renal replacement therapy (RRT) and post-transplant infection incidence.MethodsThis single-center retrospective cohort study included 158 patients who underwent heart transplantation (HTx) in our center from 2008 to 2016, survived beyond the first post-procedural day, and had available microbial data. The patients were dichotomized according to the need for periprocedural RRT. Twenty-seven patients in RRT group had lower preoperative creatinine clearance, greater body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…54 Consistent with this, we found that mechanical circulatory support in the first 48-h postheart transplantation was independently associated with the development of severe AKI, which has be reported by others. 9,21 All patients in our study who required mechanical circulatory support developed severe AKI and more than half of the severe AKI group had moderate-to-severe graft dysfunction or required mechanical support.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…54 Consistent with this, we found that mechanical circulatory support in the first 48-h postheart transplantation was independently associated with the development of severe AKI, which has be reported by others. 9,21 All patients in our study who required mechanical circulatory support developed severe AKI and more than half of the severe AKI group had moderate-to-severe graft dysfunction or required mechanical support.…”
Section: Discussionmentioning
confidence: 86%
“…Others have found an association between transfusion and AKI postheart transplantation. 3,9,27 Karkouti summarizes a large number of observational studies investigating the association of blood transfusion with AKI in cardiac surgery patients and summates that each unit of blood transfusion is independently associated with a 10% to 20% risk of AKI. 52 We found preoperative eGFR to be an independent risk factor for the development of severe AKI, this has been frequently shown by others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that risk factors for RRT after heart transplantation include history of CKD (15,16), history of hypertension (17), history of diabetes (15,16), liver disease (17), intraoperative cardiopulmonary bypass (CPB) time (16), postoperative ventricular assist device (VAD)/extracorporeal membrane oxygenator (ECMO) therapy (18) and mechanical ventilation (17). Boyle et al (16) showed that increased CPB time was an independent risk factor for RRT after HT, but this conclusion was not confirmed in the studies by Gašparović et al (19). The study conducted by Ivey-Miranda et al revealed that CKD was an independent predictor of RRT after HT (8), but Nadkarni et al cannot get this conclusion in patients who received HT (17).…”
Section: Introductionmentioning
confidence: 99%